Exploring Masculinity in JKT48 Male Fans Tweet - Aziz, Muhammad Fauzan (KnE Social Sciences, 2019)
This article further explores the function of participatory culture of fandom on cyberspace. As a part of Japanese pop-idol AKB48 franchise in Indonesia, JKT48 wasn’t popular offline, but online, specifically Twitter, JKT48 popularity were relatively high. This proved through JKT48 fans participatory practice in Twitter. Using Matt Hill’s textual productivity, this article discusses how JKT48 male fans functionalize their tweet as domination masculinity reproduction and therefore creating simulated space in Twitter. First, it sees how JKT48 dominant text reproduced by fans tweet. Second, it considers the concept of cyberspace where these tweeting practices take place. This article concludes that fans tweeting practice also reproduce domination masculinity although limited in simulated space, in order to preparing them through dominated, adult everyday lives. Keywords: Fandom; JKT48; Twitter; Participatory Culture